Non-alcoholic Fatty Liver Disease - Diagnosis and treatment: a literature review - Tavares, Lorena Fecury; Bernardo, Mariana Rosa; Pinho, Kalil Orleans Silveira; Brito, Ana Paula Santos Oliveira; Maneschy, Rodrigo Bona; Garcia, Hamilton Cezar Rocha de (Pará Research Medical Journal, 2022)
Purpose: To conduct a systematic review of the literature to gather the diagnostic and therapeutic methods of DHGNA. Methods: It was conducted a survey of the databases SciElo, LILACS and PubMED, in the Portuguese, English and Spanish languages, referring to the period from 2014 to 2018, using the following descriptors: “Non-alcoholic fatty liver disease”, “therapeutics” and “diagnosis”. Results: The search totalled 658 articles, which after data processing, remained 24 articles, of which 12 were in Spanish, 11 in English and 1 in Portuguese. Conclusion: The diagnosis of NAFLD is clinical and counts with laboratory and imaging exams, and the gold standard is the liver biopsy. Treatment consists primarily of lifestyle changes, mainly eating habits and physical activity. Pharmacological treatment is performed when changing life habits is ineffective. This includes several options, the most studied being vitamin E and Pioglitazone, while most other drugs remain with low levels of evidence. It is concluded, therefore, that there is still a lack of studies to increase the level of therapeutic recommendations of NAFLD.